Qualitative Analysis of Establishing Diagnosis and Management of Hypertension from Patient’s Perspective in Jatinangor - Yulia Sofiatin; Nazmun Lailah; Trully Deti Rose Sitorus; Rully M. A. Roesli (Faculty of Medicine Universitas Padjadjaran, 2018)
Background: Blood pressure control is necessary to prevent complications in patients with hypertension. A previous study in Jatinangor showed the failure of controlling blood pressure even with pharmacological treatment. Proper diagnosis and effective management are considered to influence the condition. This study was performed to describe the process of establishing diagnosis and management for hypertension from the patient’s perspective in Jatinangor.Methods: A phenomenological approach was used. Data were collected through semi-structured questions in focus group discussions (FGDs) led by a moderator. Participants of FGDs were patients with hypertension who had undergone antihypertensive drugs therapy based on a previous study, and were invited by the local health cadres. The study was held in two villages in Jatinangor, namely Hegarmanah and Cilayung in the period of July to August 2015. Data were presented as narration and figures.Results: There were five and eight hypertensive participants for Hegarmanah and Cilayung villages FGD, respectively. Diagnosis of hypertension in FGD participants was not only confirmed by doctors but also other health professionals, due to various accessibilities to health care facilities. Diagnosis establishment and management of hypertension were not following the protocol. Education on pharmacological and non-pharmacological management was provided by health professionals, however still lacked details and was not reviewed on every visit, resulting in a lack of compliance. Conclusions: Process of establishing diagnosis and management of hypertension from the patient’s perspective in Jatinangor is unfortunately not following the protocol, thus may influence the blood pressure control outcome.